Monitoring and sanctioning cheating at school: What works? Evidence from a national evaluation program - Claudio Lucifora; Marco Tonello (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
The diffusion of evaluation programs, along with the higher stake they account for, has also increased the prevalence of opportunistic behavior and cheating practices. This paper investigates the efficacy of different policy measures aimed at fighting cheating behaviors in schools. We exploit a classroom-based randomized experiment in Italian public schools, which assigned an external inspector to monitor the administration and marking of the tests, as well as different sanctioning mechanisms for schools suspect of cheating. We find that higher monitoring is effective in deterring cheating at all grades, while sanctions in general have no effect, and, under specific circumstances, may also trigger schools' strategic behaviors, such as selective pooling. The ineffectiveness of sanctioning schemes is explained by the fact that they are not embedded in a proper school accountability system.
Keywords: I21; I28; K42; 330; cheating; monitoring; incentives